Phosphate removal via biological process coupling with hydroxyapatite crystallization in alternating anaerobic/aerobic biofilter reactor. (April 2021) - Sun, Shaofang; Gao, Mingchang; Wang, Yue; Qiu, Qi; Han, Junli; Qiu, Liping; Feng, Yan
Highlight: A novel biofilter was designed to improve the removal efficiency of phosphate. The integrated biological and crystalline phosphate removal processes was realized. HAP crystals was biologically induced without addition of chemical reagents. Abstract: In this work, a laboratory-scale alternating anaerobic/aerobic biofilter (A/O BF) filled with self-made steel slag media was constructed, where the integrated biological and crystalline phosphorus removal process was realized to remove phosphorus and achieve phosphorus recovery from wastewater. Phosphorus accumulating organisms (PAOs) were successfully enriched within 30 days operation, the maximum phosphate removal efficiency was close to 80% under the optimal conditions with the anaerobic time of 34 h, HRT of 4 h and influent COD of 300 mg/L. The analysis of SEM-EDS and XRD indicated that hydroxyapatite (HAP) crystals were formed inside biofilms without addition of chemical reagents. The high phosphate environment created by PAOs and the release of Ca 2+ from the steel slag media might be responsible for the generation of HAP. These findings have crucial implications for the application BF technology to remove and recover phosphorus from wastewater.